Five Ways that COVID-19 Diagnostics Can Save Lives : Prioritizing Uses of Tests to Maximize Cost-Effectiveness - Reed, Tristan; Waites, William; Manheim, David; de Walque, Damien; Vallini, Chiara; Gatti, Roberta; Hallett, Timothy B. (World Bank, Washington, DC, 2021)
Supplies of diagnostic tests for SARS-CoV-2, the virus that causes COVID-19 (coronavirus), are still limited in many countries, and there is uncertainty about how to allocate the scarce supply across alternative types of testing (use cases). This Research & Policy Brief quantifies the cost-effectiveness of five alternative diagnostic use cases in terms of tests required per death averted. Across use cases, a single death can be averted by administering 940 to 8,838 tests, implying a large and positive return on investment in all use cases-even assuming a very low value for loss of life. That is, all five use cases pay for themselves many times over. When prevalence of SARS-CoV-2 is high, the most cost-effective uses of SARS-CoV-2 diagnostics seem to be clinical triage of patients, at-risk worker screening, and population surveillance. Test-trace-isolate programs and border screening are alsoworthwhile, although they are more resource intensive per death averted if done comprehensively. These latter two interventions become relativelymore cost effective when prevalence is low, and can stop the virus from entering a community completely. While governments should seekwidespread deployment of tests in all five use cases, prioritizing them in this way is likely to maximize the cost-effectiveness of their use. As morecontagious strains emerge, each use case will become more valuable than ever.